Genetic and histopathological analysis of a case of primary intraosseous carcinoma, NOS with features of both ameloblastic carcinoma and squamous cell carcinoma - Akane Yukimori; Maiko Tsuchiya; Akane Wada; Yasuyuki Michi; Kou Kayamori; Kei Sakamoto; Tohru Ikeda (World Journal of Surgical Oncology, 2020)
Abstract Background Primary intraosseous carcinoma (PIOC), NOS is an odontogenic carcinoma with unknown etiology. Its diagnosis may be used when central jaw carcinoma cannot be categorized as any other type of carcinoma. Further information on this extremely rare tumor is needed to improve our understanding and evaluate the classification of odontogenic carcinomas. Case presentation We herein presented two patients with PIOC, NOS with different clinical and histopathological features and analyzed gene mutations in these patients using next-generation sequencing (NGS). The typical PIOC, NOS case had many histopathological similarities to oral squamous cell carcinoma (OSCC), including the missense point mutations of TP53 Glu285Val, KDR Gln472His, and APC Pro1433Leu, which are similar to those in other cancers; however, no mutations were detected in the other patient with an atypical presentation of PIOC, NOS, which was derived from a precursor cystic lesion with similarities to both ameloblastic carcinoma and OSCC. Conclusions Genetic analysis suggested that these two PIOC, NOS cases have different features and can be subcategorized.